Design and implementation of wireless IoT device for women’s safety - Lisa, Jannatul Ferdaus Khan; Khan, Tahsiana Rashid; Tuba, Nishat Alam; Tonny, Prioti Saha; Mustafa, Md. Shihab (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.